2022
DOI: 10.1037/xge0001175
|View full text |Cite
|
Sign up to set email alerts
|

Letter processing in upright bigrams predicts reading fluency variations in children.

Abstract: Fluent reading is an important milestone in education, but we lack a clear understanding of why children vary so widely in attaining it. Language-related factors such as rapid automatized naming (RAN) and phonological awareness have been identified as important factors that explain reading fluency. However, whether any aspects of visual orthographic processing also explain reading fluency beyond phonology is unclear. To investigate these issues, we tested primary school children (n = 68) on four tasks: two rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…This was evidenced by weaker within‐bigram interactions in readers, which predicted their reading fluency (Agrawal et al, 2019). More recently, we have found that letter interactions in upright (not inverted) bigrams explained reading fluency variations in children even after accounting for other language based measures (Agrawal et al, 2022).…”
Section: The Blessing Of Compositionalitymentioning
confidence: 85%
“…This was evidenced by weaker within‐bigram interactions in readers, which predicted their reading fluency (Agrawal et al, 2019). More recently, we have found that letter interactions in upright (not inverted) bigrams explained reading fluency variations in children even after accounting for other language based measures (Agrawal et al, 2022).…”
Section: The Blessing Of Compositionalitymentioning
confidence: 85%
“…However, recently, evidence from psychophysics and time-resolved intracranial recordings suggests that frequent bigrams may not contribute to recognition, at least during the first ~300 ms of word recognition, where only frequent letters are separated from rare letters or non-letters (Agrawal et al, 2020;McCloskey et al, 2013;Woolnough et al, 2020). What develops with literacy is the compositionality of visual word representation, which increases the dissimilarity and independence between individual letters at nearby locations (Agrawal et al, 2019(Agrawal et al, , 2022. Compared to contextual bigram coding, ordinal letter coding provides a better fit to the psychophysical distance between letter strings (Agrawal et al, 2020), the early intracranial responses to written words (Woolnough et al, 2020), and the responses of word selective units in artificial deep networks (Hannagan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%